Pengaruh Kinerja Keuangan, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Sektor Kesehatan BEI 2020–2024 - Fitriyani Fitriyani; Muhamad Nurhamdi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to determine the effect of financial performance, capital structure, and company size on company value in healthcare companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study uses an associative quantitative approach with secondary data obtained from the company's financial statements. The sample was determined using purposive sampling, resulting in 9 healthcare companies with 45 observations. Data analysis was performed using EViews 12. Panel data regression analysis was applied using the Random Effect Model (REM), selected based on the Chow test, the Hausman test, and the Lagrange multiplier test. Furthermore, classical assumption testing and hypothesis testing were carried out. The test results show that partially Financial Performance has a significant positive effect on Company Value with a calculated T value of 2.137061 > T table 2.01954 with a prob value of 0.0386 < 0.05, Capital Structure does not have a significant effect on Company Value with a calculated T value of 0.4770233 < T table 2.01954 with a prob value of 0.6407 > 0.05, Company Size has a significant positive effect on Company Value with a calculated T value of 2.134309 > T table 2.01954 with a prob value of 0.0388 < 0.05. Simultaneously, the three independent variables have a significant positive effect on Company Value with an Fcount value of 3.059588 > Ftable 2.83 with a prob value of 0.038758 < 0.05, with a contribution of 12.31% while the remaining 87.69% is influenced by other factors outside this study.